Internações por câncer gástrico em uma mesorregião do estado do Pará - ROCHA, Amanda Negrão da (2023)
Cancer is a benign or malignant disease that can occur in any part of the body and has become increasingly present on the world stage and is even considered the leading cause of morbidity and mortality in 2012. In this way, based on data about the occurrence of cancer, it is possible to observe that it affects more and more people. When it comes to gastric neoplasm in the Brazilian population, it is among the five main causes of cancer death in the country, reaching mainly men, people over 60 and being more prevalent in the population of the North Region. Therefore, we seek to know the situation of the Marajó / PA mesoregion regarding the occurrence of gastric cancer hospitalizations from 2001 to 2016.. In order to know this number of hospitalizations, information was collected from the database of the Department of Informatics of the Unified Health System SUS (DATASUS), analyzing the variables: years of occurrence, gender and age group. It was observed that during the study period there was a gradual increase in the number of hospitalizations due to gastric cancer, with the prevalence of the years 2013 to 2016 with 42.18% of hospitalizations. Regarding gender, most hospitalizations occurred in males (66.67%) and, when evaluating the age group, hospitalizations were more frequent in people over 60 (47.69%). These findings are consistent with the results, and it was observed that in the period from 2001 to 2016 there was a gradual increase in the number of hospitalizations due to gastric cancer in the Marajó mesoregion, with the most hospitalized persons being males and those with 60 years or more.